ANALISIS KEWENANGAN DPR TERHADAP POLEMIK PENGGANTIAN HAKIM MAHKAMAH KONSTITUSI - Azis, Fuad Abdul; Ramur, Irham (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2023)
Therefore, the Indonesian constitution guarantees the independence of the judiciary from the intervention of other institutions. The polemic of the removal of a judge of the Constitutional Court by the House of Representatives has left a negative precedent in the Indonesian state administration. Moreover, Indonesia adheres to a system of separation of power or power sharing, where no one institution is higher than another state institution. Judicial power institutions are required to have freedom in carrying out their duties and functions. The dynamics of dismissing the Constitutional Court judge annulled the independence of the Constitutional Court. From the point of view of its own authority, the DPR cannot remove a judge from the Constitutional Court.